Overview of Functional Capacity and Quality of Life of Chronic Obstructive Pulmonary Disease (COPD) Patients - Rizki Rahmadani Dalimunthe; Pandiaman Pandia; Amira Permatasari Tarigan; Putri Eyanoer (Riviera Publishing, 2026)
Chronic Obstructive Pulmonary Disease (COPD) is one of the leading causes of morbidity and mortality worldwide, with a significant impact on patients’ functional capacity and quality of life. This study aims to describe the functional capacity and quality of life of COPD patients at Prof. Dr. Chairuddin P. Lubis Hospital. This study is a descriptive observational study with a serial case design. The research subjects were stable COPD patients who met the inclusion and exclusion criteria, using a convenience sampling technique. Data collected included demographic characteristics, inhaled bronchodilator therapy, functional capacity measured using spirometry and the six-minute walking distance (6MWD) test, and quality of life assessed using mMRC and CAT scores. Statistical analysis was performed using descriptive methods. A total of 110 patients participated in the study; the majority were aged 60–69 years (69.6%) and male (78%). Mean FEV?/FVC, FEV?, FVC, and 6MWD scores were higher in the tiotropium group compared with the indacaterol/glycopyrronium group. The mean CAT score indicated slightly worse quality of life in the indacaterol/glycopyrronium group (10.9 vs. 9.9). The majority of patients had cardiovascular-related comorbidities (20.9%). Tiotropium therapy showed better results in functional capacity compared with indacaterol/glycopyrronium, while quality of life was influenced by COPD severity and comorbidities. A holistic management approach that includes comorbidity management and patient education is needed to improve prognosis and quality of life. Further research is needed to explore the relationship between therapy and clinical outcomes.